Elder Mistreatment: a Clinical, Social, and Legal Concern - Muhammad Rasyid Este (Universitas Baiturrahmah, 2021)
Elder mistreatment is all activities carried out by other people towards the elderly which are classified as dangerous and causing harm, such as physical, verbal, financial or material abuse and or neglect, and violation of human rights. The incidence ranges from 3.2% to 27.5% of the elderly population, where this population is predicted to be 1.2 billion people by 2025. The main risk factors are under-reporting, individual factors, relationship factors, community factors and social factors. The diagnosis includes anamnesis of the patient, family or caregiver. Detection begins by confirming any cognitive impairment, using the Mini-Cog or Mini Mental State Examination (MMSE) form. Followed by screening, which can be done using the Elder Abuse Suspicion Index (EASI) instrument, then a physical examination looks for evidence of acts of abuse or neglect. Intervention is carried out by providing medical treatment for physical injuries, temporary protection, keeping the perpetrator away from the victim, and education on patterns of mistreatment that can involve social services and law enforcement. Management includes a complete and focused examination of mistreatment, preparing a safety plan, which is providing plans to improve patient protection, as well as education on treatment goals. Patient management should use a multidisciplinary team consisting of doctors, nurses, social workers, legal representatives and administrative officers. Complete data and clear laws and regulations regarding mistreatment are needed, such as in America and Britain where absolute mistreatment is legally reported.